Study on biochemical functions in two mosses Physcomitrium pyriforme (Hedw) Hampe. and Octoblepharum albidum (Hedw) and estimation of some heavy metals - Misra, Manjul; Tandon, PK (International Journal of Environment, 2015)
Some outskirts and highway areas of Lucknow were surveyed and two Moss Physcomitrium pyriforme and Octoblepharum albidum (Hedw.) samples were collected from some selected areas. Samples were collected from soils and moist brick walls and heavy metals Pb, Cu, and Co analyzed for the main cause of variation in biochemical functions such as chlorophyll content, Protein and catalase. Samples collected from Garden and Monument areas were treated as Control. Samples collected from outskirts and highways areas showed higher level of heavy metals in comparison to the samples collected from Garden and Monument sites. However variable results were obtained with regard to variation in biochemical functions such as chlorophyll content, protein and catalase. DOI: http://dx.doi.org/10.3126/ije.v4i2.12627 International Journal of Environment Vol.4(2) 2015: 76-86